Military Incursion into Politics: A Comparative Analysis of Civil-Military Relationship in Pakistan and Nigeria - AZEEZ, Ismail Adaramola Abdul (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Objective number one in the current study seeks to understand the role of historical developments in shaping the direction of democracy with a testable hypothesis one having that the Military intervention in politics is a result of bad politics exercised by politicians while addressing problems caused by low political culture, this paper explores answers to that question in a context of renewed option rule in Pakistan and Nigeria.Methodology:This Research paper will provide an overview of the major historical events since the independence of these two countries to be in a position to evaluate the role of the military in politics. The Nigerian military's poor human rights record has had a devastating impact on its effectiveness.Findings:Severe abuse of civilian communities, from the Ogoni (in the mid-1990s) to Odi (1999) and Zaki Biam (2001), and more recent extrajudicial assassinations, frequently in the background of contradicting militant and separatist groups from Boko Haram and the Islamic.Implication:Movement of Nigeria (IMN) In recent days, Pakistan has had legitimate power to encompass the tenures of the chiefs of staff of the army, navy, and air force.